KAJIAN TERHADAP TOOLS DAN FRAMEWORK SOCIAL MEDIA ANALYTICS UNTUK PEMANFAATAN DATA SOCIAL MEDIA DALAM PENELITIAN ILMU SOSIAL - Edi Surya Negara (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2017)
The increasing of using social media in Indonesia has the impact to the available of data about society perception toward many issues of life, even though it comes as member/personality of live and citizen in the society. These phenomena have given an opportunity for stakeholders, such as government and private that need information about the society perception or social attitudes in their social life to improve quality and quantity of information through the using of the social media. The well understanding about technology of internet, social media, databases, data structure, theories of information, data mining, machine learning, and the technique for visualization data and information are needed to get and analyze the data to determine certain information which will be used by the users (stakeholders of the information). The target of this research is to master technology of social media analytic and develop prototype of software that will be used as tools of collecting data in social media, therefore, the users of the data can focus to get comprehension/understanding about social phenomena and take decision without looking for techniques for collecting and data analysis issues. This research is designed into explanatory with focus to the understanding technology through basis of social media, moreover, it is used to review advantages and disadvantages of techniques currently used in social media and media analytic researches. The result of this research is the tools and framework that benefit for media social analysis.